Jenis Tindak Tutur dan Prinsip Kesantunan dalam Film Pendek Es Krim Terakhir dari Ayah - Rahmawati, Eka; Fatwa, Anissa Nur; Lestari, Elsa Aulia; Nadyatunnisa, Gina; Ruslan, Titin Setiartin (Jurnal Bahasa dan Sastra, 2026)
This study examines the types of speech acts and politeness principles found in the short film “Es Krim Terakhir dari Ayah | Bensurvive Series,” released on the MOP Channel in 2024. The research is motivated by the need to understand family communication patterns represented through audiovisual media that portray language use within real-life contexts. Using a descriptive qualitative method, data were collected through observation and note-taking, then analyzed using Searle’s classification of speech acts and Leech’s politeness principles. The results show 48 identified speech acts, consisting of assertive (35.4%), directive (31.3%), expressive (29.2%), and commissive acts (4.2%), while no declarative acts were found. Meanwhile, 47 data points related to politeness principles were identified, dominated by the tact maxim (27.66%), followed by the approbation and sympathy maxims (21.28% each), the modesty maxim (12.77%), the generosity maxim (10.64%), and the agreement maxim (4.26%). A total of 46 data points (97.87%) adhered to politeness maxims, while 1 datum (2.13%) violated the tact maxim. These findings indicate that the film highlights communication patterns characterized by information sharing, requests, emotional expression, and polite interaction within a family setting. The study concludes that the film portrays harmonious and empathetic family communication and contributes to pragmatic studies focusing on speech acts and politeness in audiovisual media.